Sensitivity analysis of the vane length and passage width for a radial type swirler employed in a triple swirler configuration. Issue 6 (November 2019) - Vashahi, Foad; Rezaei, Shahnaz; Dafsari, Reza Alidoost; Lee, Jeekeun
Highlights: Computational fluid dynamic (CFD) investigation on the in uence of the radial vane length and passage width on the swirling flow field of a triple swirler. Mapping the radial vane length, vane angle and swirl-jet expansion angle for predictio purposes. Control of the swirl-jet expansion angle with adjustments of the radial swirler passage width. Abstract: The design of axial or radial swirlers typically governs a number of geometrical parameters that are determined by the desired flow field. In the meantime, the number of unknown parameters increases with the number of concentrically mounted swirlers. The available literature is nonetheless limited, and designers are obligated to increase the number of initial assumptions. In this article, three kinds of triple swirlers are employed and simulations are performed to determine the effect of each parameter on the swirler performance. Based on the correlation provided, over-lengthening the radial vane length could result in significant changes in the flow field from the jet-like pattern to a wide swirl-jet angle due to the Coanda effect. Passage width should also have the potential to alter the swirl-jet angle and velocity field at the exit of the swirler.